2002
DOI: 10.1063/1.1512947
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic pinning enhancement in Nb films with arrays of submicrometric Ni lines

Abstract: Arrays of submicrometric Ni lines have been fabricated in superconducting Nb films by electron beam lithography. In the mixed state, these arrays induce strong anisotropy in the dissipation behavior. The dissipation is reduced several orders of magnitude, in the whole applied magnetic field range, when the vortex motion is perpendicular to the Ni lines ͑applied current parallel to them͒ in comparison with dissipation of vortices moving parallel to the lines. In addition, for the samples studied in this work, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 20 publications
3
33
1
Order By: Relevance
“…Furthermore, it is possible to see well defined anisotropic behavior in the critical forces, mainly for the peaks at B/B ϕ =1/3, 1/2, and 2/3. Anisotropic behavior was previously observed in experimental and theoretical for infinite films, but for higher magnetic fields and different system parameters [13][14][15][16]19,21 . Our simulations also show that, in general, F c y > F c x for fractional matching fields, with the exception of B/B ϕ =1/3.…”
mentioning
confidence: 86%
“…Furthermore, it is possible to see well defined anisotropic behavior in the critical forces, mainly for the peaks at B/B ϕ =1/3, 1/2, and 2/3. Anisotropic behavior was previously observed in experimental and theoretical for infinite films, but for higher magnetic fields and different system parameters [13][14][15][16]19,21 . Our simulations also show that, in general, F c y > F c x for fractional matching fields, with the exception of B/B ϕ =1/3.…”
mentioning
confidence: 86%
“…Some experiments examining vortices in q1D periodic pinning structures show that peaks in the critical current occur at certain fillings 53,[55][56][57] in regimes where the pinning is weak, whereas other experiments performed in the strong pinning limit reveal more step-like features in the critical current. This suggests that the experiments in the strong pinning limit are producing buckling transitions 58 .…”
Section: Pinned Phasesmentioning
confidence: 99%
“…In general, the colloidal studies focused on the case where the particle lattice constant a is larger than the substrate lattice constant w. Martinoli et al investigated vortex pinning in samples with a 1D periodic thickness modulation [53][54][55] and observed broad commensuration peaks in the depinning threshold that were argued to be correlated with the formation of ordered vortex arrangements that could align with the substrate periodicity. Other vortex studies in similar samples also revealed peaks in the critical depinning force associated with commensuration effects 56,57 , while studies of vortices interacting with 1D magnetic strips showed that commensurate conditions were marked by depinning steps rather than peaks 58 . Under an applied dc drive, depinning transitions occur into a sliding state, and when an additional ac drive is added to the dc drive, a series of Shapiro steps in the voltage-current curves appears when the frequency of the oscillatory motion of the vortex lattice moving over the periodic substrate locks with the ac driving frequency 54 .…”
Section: Introductionmentioning
confidence: 99%
“…The pinning force thus induced was minimal for flux flow parallel to the grooves and maximal for perpendicular flux flow. Jacue et al [54] fabricated submicron Ni stripes by electron beam lithography underneath superconducting Nb films and showed that the stripes induce a strong anisotropy in the dissipative behavior. When the vortices moved perpendicular to the Ni stripes the resistance dropped by several orders of magnitude in comparison with the dissipation of vortices moving parallel to them.…”
Section: Systems With Washboard Pinning Nanolandscapesmentioning
confidence: 99%